Hubungan Antara Sanitasi Dan Perilaku Pemberian Makan Terhadap Kejadian Diare Pada Balita Di Wilayah Puskesmas Kedung Banteng - Sabela Fitria Febriana; Vivi Leona Amelia (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Objective: To find out the relationship between sanitation and feeding behavior of diarrhea occurrences in toddlers in the health center of Kedung Banteng.Method:This study was a quantitative analytic study with cross sectional approach. Proportional random sampling and simple random sampling were used as the sampling method. There were 87 toddlers as the respondents in the health center of Kedung Banteng, especially in Beji Village. Chi square formula was used to test the relationship between sanitation and feeding behavior of diarrhea occurrences in toddlers.Results: There was the relationship between the sanitation of the availability of clean water (P = 0.008), sanitation of healthy latrines (P = 0,000) and feeding behavior (P = 0.013).Conclusion: Poor sanitation and feeding behavior are able to increase the diarrhea occurrences.Â